Gender Differences in Self-Regulated Online Learning During the COVID-19 Lockdown - Liu, Xiaohong; He, Wei; Zhao, Li; Hong, Jon-Chao (Frontiers in Psychology, 2021)
Due to the spread of the epidemic around the world, online learning has received greater attention. Self-regulated learning is an important factor for students to achieve academic success. This study investigated the gender differences in self-regulated learning (SRL) and three sub-constructs of SRL in the context of online learning, that is the preparatory, performance, and appraisal phases. A total of 400 high school students (males = 125, females = 275) from China participated in this study. In order to identify whether there were gender differences in their self-regulated online learning (SROL), independent sample t tests and ANOVA analysis were performed. The results showed that there were significant gender differences in the SROL (t = -3.334, p = .001 < .01, d = -.410) and the three sub-constructs of SROL (preparatory: t = -.702, p = .008 < .01, d = .018; performance: t = -3.801, p = .000 < .01, d = .456; appraisal: t = -3.120, p = .002 < .01, d = .361). The findings indicated that females performed better than males in all three dimensions of learners’ online self-regulated learning.